2014
DOI: 10.1016/j.physletb.2014.06.077
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the Higgs boson width from off-shell production and decay to Z-boson pairs

Abstract: Constraints are presented on the total width of the recently discovered Higgs boson, Gamma[H], using its relative on-shell and off-shell production and decay rates to a pair of Z bosons, where one Z boson decays to an electron or muon pair, and the other to an electron, muon, or neutrino pair. The analysis is based on the data collected by the CMS experiment at the LHC in 2011 and 2012, corresponding to integrated luminosities of 5.1 inverse femtobarns at a centre-of-mass energy sqrt(s) = 7 TeV and 19.7 invers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
163
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(170 citation statements)
references
References 43 publications
7
163
0
Order By: Relevance
“…This constrains the Higgs width to be Γ h < 17.4 MeV [158,159]. However, as with the invisible Higgs decay measurement, this interference effect does make some assumptions about the production mechanism of the Higgs [118,160].…”
Section: Higgs Mediatorsmentioning
confidence: 99%
“…This constrains the Higgs width to be Γ h < 17.4 MeV [158,159]. However, as with the invisible Higgs decay measurement, this interference effect does make some assumptions about the production mechanism of the Higgs [118,160].…”
Section: Higgs Mediatorsmentioning
confidence: 99%
“…The relevance of such a limit on g Y can be illustrated by comparing with the limits on the Higgs couplings as suggested in Refs. [64,65] and presented recently by both CMS [66] and ATLAS [67] collaborations. In these papers it has been demonstrated that a universal rescaling g SM → κg SM combined with an increase of the Higgs width by a factor κ 4 (e.g.…”
Section: The Top-pair Threshold Region and The Yukawa Couplingmentioning
confidence: 99%
“…In these papers it has been demonstrated that a universal rescaling g SM → κg SM combined with an increase of the Higgs width by a factor κ 4 (e.g. through some presently invisible mode) can be excluded for values of κ 4 exceeding 7.7 [67] or even 5.4 [66]. Such a rescaling would also involve the top quark Yukawa coupling, and it remains to be seen, if similar limits can be obtained from analysis of the top quark threshold behaviour.…”
Section: The Top-pair Threshold Region and The Yukawa Couplingmentioning
confidence: 99%
“…An extraction of the total width from experimental data (under minimal assumptions) through interference effects [12][13][14][15][16] is possible, and additional information can also be gained by including LEP data [17]. However, the current constraint from this technique is approximately Γ h < 5Γ SM h [18,19]. A precise model independent measurement of both these quantities requires input from a dedicated "Higgs machine".…”
Section: Introductionmentioning
confidence: 99%